One-year review of disability certificates issued by the neurology unit of a medical college in Maharashtra, India - Makarand M Kanjalkar; Prabhanjan V Kulkarni (Wolters Kluwer Medknow Publications, 2023)
In this article, we describe the profile of patients who were issued disability certificates from the neurology unit of a medical college in Maharashtra, India. In a retrospective cross-sectional study of 1-year duration, the demographic and clinical details of 102 participants were studied, of which 100 were issued the certificate. The mean age was 36 ± 14.04 years. There were more number of male applicants (65%) than females. Motor disability (71%) was the most common manifestation for which disability certificate was sought. Cerebral palsy was the most common etiology in the age group of <40 years, while stroke was the most common etiology in the age group >40 years. During our study period, four patients' diagnoses were changed during revisit. Additional studies are required to assess the causes of low female enrollment and lack of motivation to apply for the disability certificate at an earlier age.